SPECIAL ASPECTS OF GROWTH AND DEVELOPMENT OF CHICORY ROOT (CICHORIUM INTYBUS L.) DEPENDING ON AGROTECHNOLOGICAL CONDITIONS OF SEEDS’ GROWING - Миколайко, В. П. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
It is given the results of selectional studies on the agro technological and organizational measures for growing seeds of Chicory Root and roots surviving in the experiment without irrigation. It was established that the roots survival ranged from 93.9 to 95.3%. It wasn’t found a significant difference in this indicator, depending on the planting schemes of plants which were used for the new plants cultivation, but the high survival rate of roots ensured optimal seed density, which is close to the one planned. Similar work was held in conditions of irrigation, which helped to get similar results, but the plant surviving percentage with irrigation was higher than in control - without irrigation, while research territories in allyears of the studies were well-formed: full density of plants standing, equal placing in rows and it was provided their good development, which was the key to success in studies and it made it possible to obtainhigh yield and seed quality. It was found that both irrigation schedules and planting schemes (feeding rea) affected the height of the Chicory Root seeds, but the regulation way of plant growth and development and their flowering (pinching), practically did not effect on the change in this indicator. For both planting schemes with pinching and without it, plant height was significantly higher with irrigation. In determining the factors that affect the height of the seed depending on agricultural activities it was found that the influence of the "irrigation" was the largest and was 56.6%. The impact factor proportion of "planting schemes" was lower only 31.8%, the smallest impact was the factor of "pinching" 11.6%.